THE PROMISES AND CHALLENGES OF CROWDFUNDING FOR FINANCING SMALL BUSINESSES AND START-UPS IN UZBEKISTAN - Salokhiddin Turdiyev (PT. Antis International Publisher, 2024)
This article examines three types of crowdfunding and their beneficial aspects in financing small businesses and start-ups Uzbekistan. It delves into the practical applications and challenges of legal regulation from both legal and economic perspectives